Impact of the elements of sustainability on consumer value and satisfaction: International tourists’ perspective - Teodorović, Milivoj; Pavlović, Danijel; Popesku, Jovan (Hotel and Tourism Management, 2026)
Purpose – Previous research on sustainability, consumer value, and satisfaction of international tourists has revealed different outcomes and varying relationships. From the perspective of international tourists, the current study investigates the impact of the elements of sustainability on consumer value and satisfaction. Methodology – Based on the survey data from international tourists visiting Serbia, Partial Least Square (PLS) method determines relationship between sustainbility dimensions, consumer value and satisfaction. Findings – The results confirmed the validity, the dominant role of the economic and environmental elements, the robustness of the proposed models, and the existence of the sustainability – consumer value – satisfaction value chain. Implications – The findings contribute to the sustainability literature by highlighting previously overlooked fallouts demonstrating how the components of observed sustainability can be essential in perceived consumer value and satisfaction in an international tourist destination. The study offers a roadmap for further development and planning.